2013
DOI: 10.1159/000346998
|View full text |Cite
|
Sign up to set email alerts
|

Rapid On-Site Evaluation Improves Needle Aspiration Sensitivity in the Diagnosis of Central Lung Cancers: A Randomized Trial

Abstract: Background: Few prospective studies have evaluated the role of endobronchial needle aspiration in diagnosing central airways neoplasms. Rapid on-site evaluation has long been used in transbronchial needle aspiration of adenopathies and peripheral lesions, but its role in sampling central malignancies has not been substantiated yet. Objectives: In this study we evaluated if endobronchial needle aspiration may increase the sensitivity of bronchoscopy for diagnosing central airways neoplasms when added to convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…A recently performed RCT on EBUS-TBNA by Oki et al [49] was also, unfortunately, underpowered. Finally, the study of Mondoni et al [73] was not blinded and focused on patients with centrally located lung cancer, but showed that ROSE improved the sensitivity from 76 to 97%. Of note, although both the study of Trisolini et al [47] and the study of Yarmus et al [48] did not solely study patients with (suspected) lung cancer but contained approximately 30% other diagnoses, we feel that this is of minor influence in relation to this PICO question.…”
Section: Results Of Pico Questionmentioning
confidence: 99%
“…A recently performed RCT on EBUS-TBNA by Oki et al [49] was also, unfortunately, underpowered. Finally, the study of Mondoni et al [73] was not blinded and focused on patients with centrally located lung cancer, but showed that ROSE improved the sensitivity from 76 to 97%. Of note, although both the study of Trisolini et al [47] and the study of Yarmus et al [48] did not solely study patients with (suspected) lung cancer but contained approximately 30% other diagnoses, we feel that this is of minor influence in relation to this PICO question.…”
Section: Results Of Pico Questionmentioning
confidence: 99%
“…Two randomized trials failed to show an improvement in the diagnostic yield, but they did highlight a decrease both in procedure time and the need for additional transbronchial biopsies [12, 13]. A third randomized trial showed that ROSE improved the sensitivity from 76 to 97% [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, investigators have explored the use of rapid on‐site evaluation and the area shows promise . This could have potentially helped some of the FN cases where cellularity was a confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, investigators have explored the use of rapid on-site evaluation and the area shows promise. [17][18][19] This could have potentially helped some of the FN cases where cellularity was a confounding factor. Currently, at our institution we regularly perform adequacy assessments on our TFNAs, however, even when informed of a nondiagnostic or negative aspirate, our clinicians rarely rebiopsy patients due to a number of contributing factors such as difficult to access lesions, lesions too small to sample, low suspicion of malignancy or satisfaction with quality of tissue biopsy.…”
Section: Discussionmentioning
confidence: 99%